Mapping voluntary sector services for hidden or hard-to-reach populations: challenges and practice-based lessons for future research. (1st March 2020) - Walker, Emma J.; Waterhouse-Bradley, Bethany; Armour, Cherie
Abstract : Mapping the availability of voluntary services to a niche, potentially 'hidden' population can be a complex endeavour. This practice paper focuses on a mapping study of military-based voluntary organisations in Northern Ireland, discusses the practical challenges involved, suggests improvements to existing research practice and offers methodological guidance for others who are considering undertaking a scoping review with organisations dedicated to hidden and/or hard-to-reach populations.